2010
DOI: 10.1509/jimk.18.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of International E-Tail Performance: The Complexities of Orientations and Resources

Abstract: Retail e-commerce (e-tail) continues to grow as an important channel of distribution in the global business environment. In this article, the authors present and test a conceptual model of the relationships among firm orientations, strategic resources, and international e-tail performance. Specifically, they investigate the ability of important e-tail firm resources—brand strength and supplier relations—to mediate the effects of market orientation, entrepreneurial orientation, and foreign market orientation on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 80 publications
2
63
3
Order By: Relevance
“…The execution of the study presents some limitations. Although Pakistan and Canada are good representatives of EAMs and the Western world, respectively, further research should replicate the findings of this study in other countries (as suggested by Bianchi and Andrews [2012] and Colton, Roth, and Bearden [2010]). …”
Section: Limitations and Directions For Further Researchmentioning
confidence: 54%
“…The execution of the study presents some limitations. Although Pakistan and Canada are good representatives of EAMs and the Western world, respectively, further research should replicate the findings of this study in other countries (as suggested by Bianchi and Andrews [2012] and Colton, Roth, and Bearden [2010]). …”
Section: Limitations and Directions For Further Researchmentioning
confidence: 54%
“…The resources and performance relationship has also centered the attention of researchers in the area of export activity (Cadogan, Kuivalainen, & Sundqvist, 2009;Colton, Roth, & Bearden, 2010;Lages, Silva, & Styles, 2009;Morgan, Kaleka, & Katsikeas, 2004;Morgan, Vorhies, & Schlegelmilch, 2006;Singh, 2009;among others). However, there is a broad lack of awareness about the resources-EE relationship.…”
Section: Resources and Export Entrepreneurshipmentioning
confidence: 99%
“…Resources-results relationship is interesting for researchers on export activity (Cadogan, Kuivalainen, & Sundqvist, 2009;Colton, Roth, & Bearden, 2010). Nonetheless, resources-EE relationship suffers from a broad lack of awareness.…”
Section: Resources and Eementioning
confidence: 99%